Signs of incompatibility of grafting components in scion-rootstock combinations of pear with common quince - I. V. Semin (Овощи России, 2023)
Relevance. In the middle zone of Russia, industrial cultivation of pear fruits is almost not produced due to the lack of intensive rootstocks. In regions with a mild climate, this problem has long been solved by grafting pears on common quince, but in more northern regions, quince is not hardy enough. In recent years, as a result of the long-term work of VNIISPK scientists, winter-hardy rootstock forms of common quince have been obtained, capable of restraining the growth of grafts and accelerating their entry into the fruiting season. They have a wide prospect of being used to intensify the production of pear fruits in central Russia. However, the grafting of pears on quince is remote intergenerational and not all varieties can be cultivated on it due to different degrees of compatibility. There is no single methodology for determining compatible and incompatible graft-rootstock combinations of pear varieties with quince, therefore, it is an important and urgent task to identify signs by which non-viable combinations can be identified starting from the nursery.Materials and methods. The research was carried out in the conditions of the VNIISPK production nursery in 2008-2010; 2019-2022. The object of research was graft-rootstock combinations consisting of quince seedlings of ordinary selection of VNIISPK used as rootstocks and various varieties of pear collection of the Institute. Pear seedlings were used as a control. Propagation of varieties was carried out by the method of oculation at a height of 20 cm from the ground in the first decade of August. The repetition of the experiment is 3 times 30 plants in each. Agrotechnics of experience is generally accepted. In order to identify the most common signs characterizing the degree of compatibility of graft-rootstock combinations, starting from the awakening of the eyes of the graft, observations were made every 5-7 days on their development in a nursery.Results. In the course of observations, a number of additional signs were identified that can be indicators of positive or negative accretion of pear varieties with quince and on the basis of which it is possible to determine viable and non-viable graft-rootstock combinations already in the nursery. The conducted studies also made it possible to divide pear varieties into three groups of compatibility with quince: A – well compatible varieties. Their development on the quince rootstock is better than on the pear rootstock. B – satisfactorily compatible varieties. They can grow on common quince, that is, they can be viable graft-rootstock combinations, but there are some signs of their incomplete development. It is advisable to use a compatible insert rootstock, on which such varieties develop better. С – incompatible varieties. It is possible to grow such varieties on quince only with the use of a compatible insert rootstock. With direct grafting on common quince, such graft-rootstock combinations are not viable.